(untitled) (Journal of Nepal Geological Society, 2001)
Stratigraphy of the middle to upper part of the Kathmandu Complex around Phulchauki area was examined. Pebbly mudstone of the Tistung Formation, the lowest formation of the Phulchauki Group, was formerly regarded as evidence of the unconformity between the Bhimphedi Group and the overlying Phulchauki Group. It has, however, been elucidated as a debris flow sediment on the basis of its sedimentary structures. Stratigraphically it lies within the Lower part of Tistung Formation. It is also concluded that the Phulchauki and the Bhimphedi groups are conformable as they show lithostratigraphic and structural continuity. Preliminary palaeontological investigation of trilobites yielded from the Godavari Formation, the uppermost part of the Phulchauki Group, indicates that the youngest formation of this complex can be assigned to Late Ordovician in age. On the basis of the geologic age and lithostratigraphy, a new scheme of correlation between the Phulchauki Group and the proximal Tethys sediments distributed in the High Himalaya is proposed.